2022
DOI: 10.1177/1759720x221117879
|View full text |Cite
|
Sign up to set email alerts
|

Stromal vascular fraction therapy for knee osteoarthritis: a systematic review

Abstract: Background: Regenerative cell therapies, such as adipose-derived stromal vascular fraction (SVF), have been postulated as potential treatments for knee osteoarthritis (KOA). Objectives: To assess the efficacy and safety of SVF treatment against placebo and other standard therapies for treating KOA in adult patients. Design: A systematic review. Data sources and methods: We searched the following databases: MEDLINE via PubMed, Epistemonikos, PEDro, DynaMed, TripDatabase, Elsevier via Clinicalkey and Cochrane Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
(251 reference statements)
0
11
0
Order By: Relevance
“…We are currently improving our knowledge on the transition of treatment modalities from micro-and nano-fragmented fat tissue grafts to AD-cSVF, AD-tSVF, and ADMSCs. The number of patients in the follow-up studies is increasing [ 65 ]. There is a variation for the mean age of application in knee OA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are currently improving our knowledge on the transition of treatment modalities from micro-and nano-fragmented fat tissue grafts to AD-cSVF, AD-tSVF, and ADMSCs. The number of patients in the follow-up studies is increasing [ 65 ]. There is a variation for the mean age of application in knee OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Well-trained athletes with very few amounts of abdominal fat would not be good candidates for AD-tSVF applications [ 64 ]. Patients with secondary arthritis, medical conditions that precluded an anesthetic procedure, psychiatric disorders, history of cancer, pregnancy, coagulopathy, signs of infection or syphilis- or HIV-positive serological results, knee joint surgery, and intra-articular injection may not be a proper choice although there were no serious adverse effects reported in appropriately selected patients [ 65 , 66 , 67 ]. Cells and tissue fragments obtained from the adipose tissue are experimented to regenerate tissues related to coronary heart disease, peripheral vascular diseases, dermatopathy, chronic wounds, ischemia [ 68 ], diabetic foot ulcers, fistulas, liver fibrosis, lipodystrophy, Burger disease, and radiation-related ulcers [ 57 , 69 , 70 ].…”
Section: Adipose Derived Stromal Vascular Fraction (Ad-svf)mentioning
confidence: 99%
“…Contrary to MF-AT treatment, and as already stated in a recent systematic review, SVF is a safe and clinically and radiologically effective treatment for KOA. 1…”
mentioning
confidence: 99%
“…Contrary to MF-AT treatment, and as already stated in a recent systematic review, SVF is a safe and clinically and radiologically effective treatment for KOA. 1 For all the reasons mentioned above, we firmly believe that the statement ''compared with an enzymatically processed lipoaspirate, MF-AT secreted a higher amount of growth factors and cytokines involved in tissue repair'' can be confusing, so KOA tissue regeneration cannot be guaranteed. Authors' Response:…”
mentioning
confidence: 99%
“…Accordingly, we cannot support the statement of Boada-Pladellorens et al to consider this product as first line among the orthobiologic products for the treatment of knee OA. The same authors in a recent systematic review of the literature 1 found just 9 clinical studies investigating SVF injections for knee OA treatment, of which there were only 2 randomized controlled trials (SVF vs placebo and hyaluronic acid, respectively) with a very small number of patients (39 and 16 patients, respectively). 3,4 These underpowered studies do not allow us to draw any meaningful conclusion on the real potential of this type of adipose-derived product.…”
mentioning
confidence: 99%